Jews, Rights, and Belonging in Tunisia: Léon Elmilik, 1861-1881 - Jessica M. Marglin (L’Année du Maghreb)
Through a case study of Léon Elmilik, an Algerian Jew who made his career in Tunisia, this article contributes to the history of citizenship in the Maghrib beyond the formal, state-centered status accorded to legal citizens. Elmilik aligned himself with Jews and Christians who believed in the need to modernize and Europeanize Tunisia. He pursued this goal through his involvement in the local branch of the Alliance Israélite Universelle (an international Jewish organization based in Paris), his publications in a French Jewish newspaper, and his membership in a local masonic lodge. In all these arenas, he joined a chorus of European voices decrying the abuses of Jews at the hands of Tunisian government officials. But after he accepted a job working for a Tunisian government official in 1873, Elmilik began regularly defending the Tunisian state’s treatment of its Jews. Rather than presume that Elmilik was a janus-faced opportunist, I argue that his different, at times opposed engagements were representative of the multiple repositories in which Jews located their rights. Rights were central to the construction of belonging; by examining the various guarantors of rights to which Jews appealed, we can glimpse the multiple levels of belonging that Jews – and to some extent Muslims – cultivated in the pre-colonial Maghrib.